Author Correction: BCAT1 restricts αKG levels in AML stem cells leading to IDHmut -like DNA hypermethylation - Raffel, Simon; Lutz, Christoph; Poschet, Gernot; Jensen, Patrizia; Fröhling, Stefan; Wuchter, Patrick; Lichter, Peter; Hell, Rüdiger; Herrmann, Carl; Ho, Anthony Dick; Krijgsveld, Jeroen (Nature, 2018)
In Extended Data Fig. 1a of this Letter, the flow cytometry plot depicting the surface phenotype of AML sample DD08 was a duplicate of the plot for AML sample DD06. Supplementary Data 4 has been added to the Supplementary Information of the original Letter to clarify the proteome data acquisition and presentation. The original Letter has been corrected online.